Always [compact disc] - Tomlin, Chris, 1972- (Sparrow, 2022)
Chris Tomlin, Christian music's biggest artist, returns (after his number one album, Chris Tomlin & Friends) with fresh songs including Always; and Holy Forever. Featuring special guests Elevation Worship, Steffany Gretzinger, and Brandon Lake.